Calycosin Orchestrates Osteogenesis of Danggui Buxue Tang in Cultured Osteoblasts: Evaluating the Mechanism of Action by Omics and Chemical Knock-out Methodologies - Gong, Amy G. W.; Duan, Ran; Wang, Huai Y.; Dong, Tina T. X.; Tsim, Karl W. K. (Frontiers in Pharmacology, 2018)
Danggui Buxue Tang (DBT), an ancient Chinese herbal decoction commonly used to mitigate menopausal osteoporosis, contains 2 herbs: Astragali Radix (AR) and Angelicae Sinensis Radix (ASR). The exact efficacy of individual chemical(s) within DBT, or in any herbal mixture, is hard to be revealed. Calycosin and ferulic acid have been reported to be the predominant chemicals found within DBT, and its roles in regulating osteoblastic differentiation have been proposed here. To probe the roles of calycosin and ferulic acid, these chemicals were specifically depleted from the DBT extracts. Here, calycoisn-depleted DBT (DBT∆cal) and ferulic acid-depleted DBT (DBT∆fa), generated by semi-preparative HPLC, were coupled with RNA-seq and metabolomics analyses to reveal the synergistic functions of individual chemicals within a complex herbal mixture. The expressions of osteogenic differentiation markers were significantly increased under the treatments of DBT and DBT∆fa. The DBT-induced genes were markedly reduced in the absent of calycsoin, i.e. DBTΔcal. In cultured osteoblasts, the DBT-activated Wnt/β-catenin and MAPK/Erk and signaling pathways were greatly affected when calycosin was depleted. By metabolomics analysis in DBT-treated osteoblasts, the profile of metabolites triggered by DBTΔcal showed distinction to that of DBT and/or DBT∆fa. Thus, our findings indicated that calycosin, rather than ferulic acid, could be an indispensable chemical in DBT to orchestrate multi-components of DBT in achieving maximal osteogenic properties.